SOME OBSERVATIONS ON THE SOCIOLOGY OF SAMPLING. - Alpert, Harry (Social Forces)
In suggesting a symposium on "Sampling in Social Structures," researcher Robert C. Angell defined the problem as one of getting at social structure by sampling methods. The cultural anthropologist has usually tried to cover the whole structural picture in his primitive tribe, but in modern society that is too laborious a task. Shortcuts must be discovered in this field that are analogous to the shortcut of public opinion sampling. For the most part, anthropologists have generalized about the total social organization of a tribe on the basis of uncontrolled samplings. Rare, indeed, if at all existent, is the anthopological study in which informants were selected on a random or systematic basis. The biases involved in the use of paid informants or in the recording of experiences of those natives who happen to be conveniently available are, for the most part, unexplored. The author's remarks are confined to some general observations on the importance of introducing considerations of social structure into the development of sampling designs for surveys involving social organizations. The basic thesis is that sociological theory must enter into, govern and guide the development of the appropriate sample design for a given survey purpose.